2000
DOI: 10.1021/jp9942522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Threonine 203 Replacements on Excited-State Dynamics and Fluorescence Properties of the Green Fluorescent Protein (GFP)

Abstract: We report a comparative study of wild-type green fluorescent protein (GFP) and single-site mutants in which threonine at position 203 has been replaced by aliphatic and aromatic residues, i.e., by valine (V), isoleucine (I), phenylalanine (F), tyrosine (Y), and histidine (H). Steady-state absorption spectra reveal changes that reflect different charge distributions in the mutants as compared to wild-type GFP. While the absorption peak of the protonated fluorophore, RH, undergoes only a small red shift in all T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
125
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 30 publications
20
125
0
Order By: Relevance
“…S4) diminish the functional relevance of a phenolic ring wag in the Ca 2+ -free GEM-GECO1, which instead adopts a 170 cm −1 in-plane rocking motion to drive ESPT (SI Text) but less efficiently. This is in accord with previous reports of longer ESPT time in wtGFP upon T203V mutation (17,18).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…S4) diminish the functional relevance of a phenolic ring wag in the Ca 2+ -free GEM-GECO1, which instead adopts a 170 cm −1 in-plane rocking motion to drive ESPT (SI Text) but less efficiently. This is in accord with previous reports of longer ESPT time in wtGFP upon T203V mutation (17,18).…”
Section: Discussionsupporting
confidence: 94%
“…Therein, the Ca 2+ -free protein modes exhibit a time constant of 30-40 ps attributed to ESPT, much longer than the 5-9 ps counterpart for wtGFP in water (22,26). In contrast, the Ca 2+ -bound protein shows characteristic mode decay on the 500-900 ps timescale, revealing that ESPT is essentially blocked and blue emission from A* dominates (17,19).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As GCaMP2 is largely monomeric under typical imaging conditions, the Ca 2ϩ -monomer structures served as the basis for mutagenesis studies to address function. All mutations were made in the context of GCaMP2-T116V (gfp T203V), a mutation previously described to increase the wild type EGFP excited-state proton transfer (32)(33)(34). 3 We created groups of GCaMP2 mutants to test three hypotheses about GCaMP function: (a) that mutating CaM or the cpEGFP-CaM linker to block solvent access to the EGFP chromophore would improve brightness ("solvent access" mutants), (b) disrupting the cpEGFP-CaM interfaces seen in the crystal structure would decrease sensor performance ("interface" mutants), and (c) mutating EGFP ␤-barrel positions observed to be solvent-exposed in the GCaMP2 structure (but not in EGFP itself) due to the circular permutation would alter sensor function ("inner barrel" mutants).…”
Section: Structural Analysis Of Monomeric Ca 2ϩmentioning
confidence: 99%
“…23 For instance, the effect of Threonine 203 was reported. 24 It was found that T203F and T203Y could stabilize the deprotonated form, while T203V, T203I and …”
Section: Resultsmentioning
confidence: 99%